(untitled) (Baghdad Science Journal, 2005)
This research aims to identify the nutritional status of the individual’s relationship to malnutrition using anthropometric measurements such as weight, height and impact on the values ??of the blood study sample included 200 male and 200 female of the inhabitants of the cities of Baghdad and Baquba reviewers Central Mahtbrat